Sublethal Effects of Triflumezopyrim on Biological Traits and Detoxification Enzyme Activities in the Small Brown Planthopper Laodelphax striatellus (Hemiptera: Delphacidae) - Zhang, Shuirong; Wang, Xuegui; Gu, Fuchuan; Gong, Changwei; Chen, Lin; Zhang, Yuming; Hasnain, Ali; Shen, Litao; Jiang, Chunxian (Frontiers in Physiology, 2020)
The gray planthopper [Laodelphax striatellus (Fallén) (Hemiptera, Delphacidae)] is one of the most destructive insect pests of rice and has developed serious resistance to several kinds of chemical insecticides. Triflumezopyrim, a novel mesoionic insecticide developed by DuPont Crop Protection, has an efficient biological activity to control sucking insects, such as the planthopper. However, the effects of triflumezopyrim on the growth and reproduction of L. striatellus have not been reported. In this study, an age-stage life table procedure was used to evaluate the effects of a sublethal concentration (LC50) of triflumezopyrim on the biological parameters of L. striatellus. The results showed that the fecundity and egg hatching ability of F5 generation (Tri-Sel) were significantly decreased and that the average duration of life (T) was not significantly affected compared with those of susceptible laboratory strain (Sus-Lab). Moreover, the finite rate of increase (λ) and the net reproductive rate (R0) were all significantly decreased in the Tri-Sel strain. The detoxification enzyme activities and contents of vitellogenin (Vg) and vitellogenin receptor (VgR) in the Sus-Lab and Tri-Sel strain female adults were also detected, and the results showed that the activities of GSTs and P450s in the Tri-Sel strain were significantly increased (P < 0.05), whereas the contents of Vg and VgR in the Tri-Sel strain were significantly decreased (P < 0.05) compared to those in the Sus-Lab strain. Furthermore, we also detected the relative expression of ecdysone receptor (EcR), Vg and VgR in the Sus-Lab and Tri-Sel strains and found that the relative expression levels of Vg and VgR in Tri-Sel female adults were obviously lower than those in the Sus-Lab strain (P < 0.05), whereas the relative expression of EcR was slightly increased, with no significant difference (P > 0.05). Based on these results, a sublethal concentration (median lethal concentration, LC50) of triflumezopyrim could inhibit the population development of L. striatellus. Moreover, our results also provide a reference for further studies on the suitability and resistance mechanisms of L. striatellus subjected to a sublethal dose of triflumezopyrim.